The Effect of Using The 6 Steps of Hand Washing Video on The Hand Washing Skills of Preschool Children at Pertiwi Kindergarten, Keputran, Kemalang: Pengaruh Penggunaan Video 6 Langkah Cuci Tangan Terhadap Keterampilan Cuci Tangan pada Anak Prasekolah di Tk Pertiwi Keputran Kemalang - Renantyas, Jatiningsih; Suryani, Eko; Badi'ah, Atik (Poltekkes Kemenkes Yogyakarta, 2023)
In 2018 there was an increase in the incidence of infectious diseases such as diarrhea from 4.5% to 6.8%. This is because the behavior of washing hands is still minimally practiced by the community, especially children. Around 400 million children in developing countries are infected with intestinal worms due to lack of knowledge and skills on how to wash their hands properly. The purpose of this study was to determine the effect of using the 6-step hand washing video on hand washing skills in preschool children at Pertiwi Kindergarten Keputran Kemalang. This type of research is quantitative research using a design with